ANALYSIS OF X GENERATION IN FILM “TURAH” - Patawari, Muhammad Yunus (Capture : Jurnal Seni Media Rekam, 2018)
The film is one of the media that can describe a generation of speech in an era. The stuttering of the older generation is often described as conservative-minded actors facing the changing times. On the other hand, the uncertainty of the young generation facing their own times is loaded with inherited values which are always in conflict with the principles of modern life. This paper tries to analyze how these generations are presented into the film. Taking the film Turah as a research material, the author wants to analyze further how the character of the figures in this film represents his generation. The author uses two sets of analysis, that is generation theory David and Jonah Stillman to identify generations and their characteristics. Secondly, the analysis of Christian Metz's shot to examine the relations of generation in the film Turah. Turah is the main character in the film representing the generation of X (middle aged). Generation X has a role as a bridge between the generations above it and the generation below it (millennial). The generation X's ability to absorb its predecessor values to be inherited to the millennials generations will shape the character of the generation Z, the farthest generation of its predecessors.